(untitled) (Jurnal AbdiMas Nusa Mandiri, 2025)
This community service program focused on the entrepreneurial development of the Jagong Family Farmer Group in Tebing Tinggi. The program was designed to address the group’s limited knowledge and skills in modern business management and low digital literacy for online marketing. The methodology involved intensive training and mentoring in corn emping production, financial, and marketing management, along with fundamental digital training encompassing social media utilization and e-commerce introduction. The results indicate a quantifiable and significant improvement: the average knowledge score of the group members regarding business management and digital marketing increased by 63.46% (from 52 to 85). This enhanced capacity also resulted in better management of production, finance, and marketing, with social media utilization successfully increasing product promotional reach by 35%. In conclusion, the training successfully transformed the Jagong Family Farmer Group from traditional farmers into professional, economically independent, and digitally competitive business actors. This increase in digital literacy and business management skills provides a direct and positive contribution to the Sustainable Development Goals (SDGs), specifically in food security and economic growth.